16 Incidence of thromboembolism following detection by trans-oesphageal echocardiography of left atrial thrombus. (7th October 2015) - Mahon, C; Erwin, J; Keane, D
Abstract : Objective: To our knowledge no study has looked at the incidence of ischaemic stroke following the detection of LAA thrombus. The purpose of this retrospective study is to determine the incidence of ischaemic stroke over a six month period following a confirmed diagnosis of LAA thrombus. Method: This was a ten year retrospective single centre study between March 2005 and February 2014 in St. Vincent's University Hospital, Ireland. All TOE studies performed during this period were reviewed. A chart review was carried out on any patient who had a LAA thrombus, LA thrombus or pre-thrombus state identified. Charts were reviewed for documented neurological deficits consistent with ischaemic stroke or transient ischaemic attack within six months of the TOE study. Results: Overall 1, 903 TOE studies were reviewed. A total of 67 TOE studies detected a LAA thrombus, LA thrombus or pre-thrombus state. In the days prior to their TOE, an ischaemic stroke had occurred in two of the patients. Following detection of thrombus or pre-thrombus state on TOE, no patient had an ischaemic stroke over the subsequent six months. Conclusion: Our study demonstrates low stroke rates over a six month follow-up period in patients with a confirmed LAA thrombus or pre-thrombus state on OAC.